Reversibility of hepatitis B virus cirrhosis after therapy: who and why? - Pierre Bédossa (2014)
Abstract The end point of liver fibrosis in almost all chronic liver diseases including HBV chronic hepatitis is cirrhosis. Progression to cirrhosis is associated with annular deposition of fibrous tissue and vascular remodeling with a shift from a lobular to nodular organization. Although advanced liver fibrosis was previously thought to be irreversible, today there is compelling evidence that cirrhosis can be reversed if the underlying cause of liver injury is eliminated. Indeed, most clinical trials with antiviral therapy and histological follow‐up have shown that fibrosis can regress and that in some cases even cirrhosis can reverse following long‐term HBV ‐ DNA suppression, although the return to a fully normal liver is rarely observed and difficult to prove. Nevertheless, a marked percentage of cirrhosis will not reverse even after effective antiviral therapy. Generally cirrhosis is more likely to regress if it is recent, there is effective and long‐lasting viral suppression, an internal capacity to regenerate and no vascular thrombosis. HBV treatment in patients with cirrhosis is associated with an improved clinical outcome although there may still be a risk of hepatocellular carcinoma. Nevertheless it has not yet been determined if a favorable outcome depends on histological regression or whether the reversal of cirrhosis is merely a surrogate marker of viral suppression. The significance of the reversal of cirrhosis is still a subject of debate because neither the histological scoring systems nor non‐invasive markers to evaluate the reversal of cirrhosis have been validated.